2017
DOI: 10.18632/oncotarget.22686
|View full text |Cite
|
Sign up to set email alerts
|

RIP140 and LCoR expression in gastrointestinal cancers

Abstract: The transcription coregulators RIP140 and LCoR are part of a same complex which controls the activity of various transcription factors and cancer cell proliferation. In this study, we have investigated the expression of these two genes in human colorectal and gastric cancers by immunohistochemistry. In both types of tumors, the levels of RIP140 and LCoR appeared highly correlated. Their expression tended to decrease in colorectal cancer as compared to adjacent normal tissues but was found higher in gastric can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…Correlations of LCoR and RIP140 expression have been described in studies on breast, cervical, and gastrointestinal cancer (Jalaguier et al 2017;Triki et al 2017;Vattai et al 2017). In our study, we detected a negative correlation between nuclear LCoR and cytoplasmic RIP140 expression (p = 0.005).…”
Section: Discussionsupporting
confidence: 77%
“…Correlations of LCoR and RIP140 expression have been described in studies on breast, cervical, and gastrointestinal cancer (Jalaguier et al 2017;Triki et al 2017;Vattai et al 2017). In our study, we detected a negative correlation between nuclear LCoR and cytoplasmic RIP140 expression (p = 0.005).…”
Section: Discussionsupporting
confidence: 77%
“…We previously reported that NRIP1 negatively regulates the Wnt/β-catenin signaling pathway and exerts an important role in normal and malignant development of intestinal epithelium [23]. In CRC, NRIP1 is a good prognostic marker because its expression is significantly correlated with better overall survival (OS) [23,24]. These data dealing with the role of NRIP1 in CRC have been obtained mainly in a context of sporadic CRC, independently of the MSI status.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, NRIP1 interacts with E2F transcription factors, suppressing their transcriptional function and also suppresses proliferator activated receptor gamma (PPARG) through receptor coactivator 1 (NCOA1), thereby inhibiting cell proliferation (13). This kind of dysregulation may affect other signaling pathways, such as NOTCH, p53, Hedgehog and Hippo, resulting in up-regulation of their expression on cancer cells (14). According to many studies, NRIP1 is engaged in the development and progression of solid tumors (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…NRIP1 is considered an essential transcriptional co-factor for estrogen signaling (11,20). It has been found that it interacts mainly with ERβ and may also act as a tumor suppressor in ovarian and colonic cancer (14,21). Specifically, in ovarian cancer NRIP1 may be involved in the suppression of ERα activity through ERβ (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation